High performance disability sport coaching - Kohe, Geoffery Z. 1983-; Peters, Derek M. (London Routledge, 2017)
As the profile of disability sport has risen, so has the emphasis grown beyond participation to include the development of a high performance environment. This book is the first to take an in-depth look at the role of coaches and coaching in facilitating the professionalisation of disability sport, in raising performance standards, and as an important vector for the implementation of significant political, socio-cultural and technological change. Using in-depth case studies of elite disability sport coaches from around the world, the book offers a framework for critical reflection on coaching practice as well as the reader's own experiences of disability sport. The book also evaluates the vital role of the coach in raising the bar of performance in a variety of elite level disability sports, including athletics, basketball, boccia, equestrian sport, rowing, soccer, skiing, swimming and volleyball. Providing a valuable evidence-based learning resource to support coaches and students in developing their own practice, High Performance Disability Sport Coaching is essential reading for all those interested in disability sport, coaching practice, elite sport development and the Paralympic Games.
Introduction / Derek M. Peters & Geoffery Z. Kohe -- Going the Distance : A Tale of Energy, Commitment and Collaboration / Drew Ferguson, Laura G. Purdy, Jennifer Purdy & Paul Potrac -- Creating a High Performance Para-Rowing Programme in the USA : From the Geography of the Land to the Generosity of the Spirit (and everything in between) / Natalie J. Campbell -- Coaching Across the Species Barrier : Para-Equestrian Dressage (Georgina Holmes) -- "Just doing it" : A Strength Based Approach to Coaching Athletes / Tania Cassidy, Lisette Burrows, Raylene Bates & Joan Merrilees -- On the Way to Rio 2016 : Coaching Paralympic Volleyball in Brazil / Carla Filomena Silva -- Coaching Wheelchair Basketball Players : From Beginning to the Top / Hana Válková, Jakub Válek & Stepán Válek -- Coaching in the Flagship Paralympic Sport : A Tale from Trackside / P. David Howe -- Ozzie Sawicki, Coaching Alpine Skiing : The Curiosity to Be the Best / David F.H. Legg & Bradley M.J. McClure -- Glynn Tromans : In Search of "Fearless" Boccia and the "Big Hairy Audacious Goal" / Ian Brittain -- From Melksham to Rio : A Coach's 20-year Journey in Para-Swimming / Anthony J. Bush -- Beyond High Performance Disability Sports Coaching? / Geoffery Z. Kohe & Derek M. Peters.
Includes bibliographical references and index.
Keywords: Sports for people with disabilities -- Coaching; Athletes with disabilities -- Health and hygiene